-10(s+4)=-106

Simple and best practice solution for -10(s+4)=-106 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(s+4)=-106 equation:


Simplifying
-10(s + 4) = -106

Reorder the terms:
-10(4 + s) = -106
(4 * -10 + s * -10) = -106
(-40 + -10s) = -106

Solving
-40 + -10s = -106

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '40' to each side of the equation.
-40 + 40 + -10s = -106 + 40

Combine like terms: -40 + 40 = 0
0 + -10s = -106 + 40
-10s = -106 + 40

Combine like terms: -106 + 40 = -66
-10s = -66

Divide each side by '-10'.
s = 6.6

Simplifying
s = 6.6

See similar equations:

| Z^4=6z^2+7 | | 5(y+-4)=35 | | 5y+4=35 | | 27=3(2x-3) | | 4-5x+20-6x=68 | | 8x+28=4(x+5) | | -36=8x-11x | | 8(x-10)=-92 | | (x-8)+x+(x+x-8)*0.75=70 | | (x^2+x)-(x+2)=0 | | (1,06²²-1)/(1,06²²,065) | | 7/2x=105 | | 2x+3(4+4)=2x+3(4) | | 422/x=9 | | -10x=10-10 | | Tan-1(8/3)=69.4 | | 2(4x-5)=-38 | | x^2+y^2+4x+5=0 | | 10+(x-1)10=200 | | log^3x=17 | | 6(3n-1)=4(n+4) | | 8+5y=8900 | | 15x-1=9-5x | | 3q=11q | | 18x^2+25x-15=0 | | 4(2x-6)=3c | | 73*10+6+-13=723 | | 73*10+6-13=723 | | 4c+4d+2c-8d= | | z+2iz=2i+1 | | 9x-100=3x-10 | | -3-4x=5-6x |

Equations solver categories